(untitled) (Journal of Partial Differential Equations, 2003)
" The elliptic differential equations of second order sum^n_i,j=1D_i[A_ij(x, y)D_jy] + P(x, y) + Q(x, y, 2207y) = e(x), x 2208 03a9 . will be considered in an exterior domain 03a9001a2282 R^n, n 2265 2. Some oscillation criteria are given by integral averaging technique."